2013
DOI: 10.1186/1743-0003-10-46
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in muscle atrophy and muscle fiber type conversion after spinal cord transection and peripheral nerve transection in rats

Abstract: BackgroundSpinal cord transection and peripheral nerve transection cause muscle atrophy and muscle fiber type conversion. It is still unknown how spinal cord transection and peripheral nerve transection each affect the differentiation of muscle fiber type conversion mechanism and muscle atrophy. The aim of our study was to evaluate the difference of muscle weight change, muscle fiber type conversion, and Peroxisome proliferator-activated receptor-γ coactivatior-1α (PGC-1α) expression brought about by spinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
4
15
0
Order By: Relevance
“…To gain insight into known regulators of type I fiber expression and mitochondrial status, we evaluated PGC‐1α and PGC‐1β protein expression, which regulate type I fiber gene expression and mitochondrial biogenesis (Kang, Goodman, Hornberger, & Ji, ; Lin et al, ), and mitochondrial function (Gali Ramamoorthy et al, ), respectively. In spinalized rodents, PGC‐1α protein levels are suppressed within two weeks (Higashino et al, ), with 50% lower total and nuclear PGC‐1α protein expression (Wu et al, ) and 50% lower PGC‐1β mRNA (Wu et al, ) persisting for at least 8 weeks. In our primary study, PGC‐1α expression appeared relatively lower at 8 weeks after severe SCI versus SHAM and near‐identical in SCI+TE+TM and SHAM groups, although these differences were not significant and were less pronounced than after spinal transection.…”
Section: Discussionmentioning
confidence: 99%
“…To gain insight into known regulators of type I fiber expression and mitochondrial status, we evaluated PGC‐1α and PGC‐1β protein expression, which regulate type I fiber gene expression and mitochondrial biogenesis (Kang, Goodman, Hornberger, & Ji, ; Lin et al, ), and mitochondrial function (Gali Ramamoorthy et al, ), respectively. In spinalized rodents, PGC‐1α protein levels are suppressed within two weeks (Higashino et al, ), with 50% lower total and nuclear PGC‐1α protein expression (Wu et al, ) and 50% lower PGC‐1β mRNA (Wu et al, ) persisting for at least 8 weeks. In our primary study, PGC‐1α expression appeared relatively lower at 8 weeks after severe SCI versus SHAM and near‐identical in SCI+TE+TM and SHAM groups, although these differences were not significant and were less pronounced than after spinal transection.…”
Section: Discussionmentioning
confidence: 99%
“…Karlsson et al [30] included both WAD II and III while Elliott et al [27] included only WAD II. Therefore, morphological changes might be expected to be greater in the group with positive neurological signs (WAD III) but this was not the case [47]. Only 50% of the Matsumoto et al [31] cohort reported head, neck or shoulder pain at 10 year follow-up.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Therefore, in the present study, we established a denervated muscle atrophy model using sciatic nerve disruption in mice, followed by intraperitoneal injection. The atrophy of soleus muscle, containing 98% slow type muscle fibers, was greater affected by sciatic nerve transection as compared to tibialis anterior and extensor digitorum longus muscles (Beehler et al, 2006;Higashino et al, 2013). The wet weight ratio, muscle fiber cross-sectional area (CSA), mitophagy, and muscle fiber type conversion of the soleus muscle were investigated to evaluate the protective effect of isoquercitrin on denervated muscle atrophy.…”
Section: Introductionmentioning
confidence: 99%